Targeting atypical protein kinase C iota reduces viability in glioblastoma stem-like cells via a notch signaling mechanism - Phillips, Emma; Lang, Verena; Bohlen, Jonathan; Bethke, Frederic; Puccio, Laura; Tichy, Diana; Herold-Mende, Christel; Hielscher, Thomas; Lichter, Peter; Goidts, Violaine (International journal of cancer, 2016)
In a previous study, Protein Kinase C iota (PRKCI) emerged as an important candidate gene for glioblastoma (GBM) stem-like cell (GSC) survival. Here, we show that PKCι is overexpressed and activated in patient derived GSCs compared with normal neural stem cells and normal brain lysate, and that silencing of PRKCI in GSCs causes apoptosis, along with loss of clonogenicity and reduced proliferation. Notably, PRKCI silencing reduces tumor growth in vivo in a xenograft mouse model. PKCι has been intensively studied as a therapeutic target in non-small cell lung cancer, resulting in the identification of an inhibitor, aurothiomalate (ATM), which disrupts the PKCι/ERK signaling axis. However, we show that, although sensitive to pharmacological inhibition via a pseudosubstrate peptide inhibitor, GSCs are much less sensitive to ATM, suggesting that PKCι acts along a different signaling axis in GSCs. Gene expression profiling of PRKCI-silenced GSCs revealed a novel role of the Notch signaling pathway in PKCι mediated GSC survival. A proximity ligation assay showed that Notch1 and PKCι are in close proximity in GSCs. Targeting PKCι in the context of Notch signaling could be an effective way of attacking the GSC population in GBM.